Site Evaluation for Nuclear Installations : Safety Requirements. - IAEA (IAEA Safety Standards Series No. NS-R-3 (Rev. 1), 2016)
"This publication establishes requirements and provides criteria for ensuring safety in site evaluation for nuclear installations. The Safety Guides on site evaluation listed in the references section provide recommendations on how to meet the requirements established in this publication. A review of Safety Requirements publications was commenced in 2011 following the accident in the Fukushima Daiichi nuclear power plant in Japan. The review revealed no significant areas of weakness and resulted in just a small set of amendments to strengthen the requirements and facilitate their implementation, which are contained in the present publication."--Publisher's description.